2018
DOI: 10.1155/2018/2656425
|View full text |Cite
|
Sign up to set email alerts
|

Molding of Polymeric Composite Reinforced with Glass Fiber and Ceramic Inserts: Mathematical Modeling and Simulation

Abstract: This work provides a numerical study of a polymer composite manufacturing by using liquid composite material molding. Simulation of resin flow into a porous media comprising fiber perform (reinforcement) inserted in a mold with preallocated ceramic inserts has been performed, using the Ansys FLUENT® software. Results of resin volumetric fraction, stream lines and pressure distribution inside the mold, and mass flow rate (inlet and outlet gates) of the resin, as a function of filling time, have been presented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…On the contrary, for the second domain (without gaps) at the beginning the flow took the shape of a semi-circle until reach the boundary of the mold, then the flow became almost the same at all points. This shape of flow is similar to that of Porto et al [55] and Tuncol et al [39]. Also, from ANSYS FLUENT the time needed to complete filling of mold in case 1 (with gaps) is 1802 sec while the time needed for case 2 (without gaps) is 5014 sec that means there is a time saving about 178.25% from this result, it can be concluded that the gaps produced by (making the fiber dimensions smaller than the mold) can be used to reduce the mold filling time without affecting the mechanical properties.…”
Section: Processing Time Theoreticallysupporting
confidence: 88%
“…On the contrary, for the second domain (without gaps) at the beginning the flow took the shape of a semi-circle until reach the boundary of the mold, then the flow became almost the same at all points. This shape of flow is similar to that of Porto et al [55] and Tuncol et al [39]. Also, from ANSYS FLUENT the time needed to complete filling of mold in case 1 (with gaps) is 1802 sec while the time needed for case 2 (without gaps) is 5014 sec that means there is a time saving about 178.25% from this result, it can be concluded that the gaps produced by (making the fiber dimensions smaller than the mold) can be used to reduce the mold filling time without affecting the mechanical properties.…”
Section: Processing Time Theoreticallysupporting
confidence: 88%
“…Although researches on the transparent concrete have obtained some achievements over the past decades, transparent concrete cannot be regarded as a mature building material. e method mentioned above can achieve the production of transparent resin concrete [11][12][13]. However, the primary focus of the transparent concrete technology previously has been on its aesthetic appeal and its application in artistic design [14][15][16].…”
Section: Introductionmentioning
confidence: 99%